The Postoperative Pain Assessment Skills Pilot Trial. (2011) - McGillion, Michael; Dubrowski, Adam; Stremler, Robyn; Watt-Watson, Judy; Campbell, Fiona; McCartney, Colin; Victor, J Charles; Wiseman, Jeffrey; Snell, Linda; Costello, Judy; Robb, Anja; Nelson, Sioban; et al.
Abstract : BACKGROUND/OBJECTIVES: Pain-related misbeliefs among health care professionals (HCPs) are common and contribute to ineffective postoperative pain assessment. While standardized patients (SPs) have been effectively used to improve HCPs' assessment skills, not all centres have SP programs. The present equivalence randomized controlled pilot trial examined the efficacy of an alternative simulation method – deteriorating patient-based simulation (DPS) – versus SPs for improving HCPs' pain knowledge and assessment skills. METHODS: Seventy-two HCPs were randomly assigned to a 3 h SP or DPS simulation intervention. Measures were recorded at baseline, immediate postintervention and two months postintervention. The primary outcome was HCPs' pain assessment performance as measured by the postoperative Pain Assessment Skills Tool (PAST). Secondary outcomes included HCPs knowledge of pain-related misbeliefs, and perceived satisfaction and quality of the simulation. These outcomes were measured by the Pain Beliefs Scale (PBS), the Satisfaction with Simulated Learning Scale (SSLS) and the Simulation Design Scale (SDS), respectively. Student's t tests were used to test for overall group differences in postintervention PAST, SSLS and SDS scores. One-way analysis of covariance tested for overall group differences in PBS scores. RESULTS: DPS and SP groups did not differ on post-test PAST, SSLS or SDS scores. Knowledge of pain-related misbeliefs was also similar between groups. CONCLUSIONS: These pilot data suggest that DPS is an effective simulation alternative for HCPs' education on postoperative pain assessment, with improvements in performance and knowledge comparable with SP-based simulation. An equivalence trial to examine the effectiveness of deteriorating patient-based simulation versus standardized patients is warranted.